2009
DOI: 10.1590/s0004-27302009000200010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adiposity on immunological parameters

Abstract: Studies evaluating immune function in obese humans and experimental animals indicate that the excess adiposity is associated with impaired in immune responses. Obesity is related to a higher rate of infections and to some types of cancer. Nutritional, metabolic and endocrine factors are implicated in the immunological changes. The adipose tissue directly produces substances with various functions related to immune system. Furthermore, some investigations suggest that certain types of weight reduction strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 51 publications
3
31
0
3
Order By: Relevance
“…Our findings are in line with the results of many previous studies as Moulin et al who showed in his study that obesity is associated with the modulation of immune parameters (33), elevated numbers of circulating immune cells as neutrophil, monocyte, leukocyte and total WBC (34,35), as well as elevated activation levels of certain WBC and suppressed immune cell function (15). Also, several authors have reported a chronic inflammation status in individuals with higher BMI (36-38) which was associated with elevated amounts of white blood cells, neutrophils, and monocytes in the blood of all participants with BMI higher than that of the control group (39).…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are in line with the results of many previous studies as Moulin et al who showed in his study that obesity is associated with the modulation of immune parameters (33), elevated numbers of circulating immune cells as neutrophil, monocyte, leukocyte and total WBC (34,35), as well as elevated activation levels of certain WBC and suppressed immune cell function (15). Also, several authors have reported a chronic inflammation status in individuals with higher BMI (36-38) which was associated with elevated amounts of white blood cells, neutrophils, and monocytes in the blood of all participants with BMI higher than that of the control group (39).…”
Section: Discussionsupporting
confidence: 94%
“…The maturation of monocytes into macrophages was found to be lower, and the capacity of polymorphonuclear (PMN) to be bactericidal was found to be reduced in obese individuals [28,29]. Severely obese individuals also have a significant decrease in NK cell activity compared with control individuals after adjustment for age and gender [30]. People with diabetes mellitus are also easily affected by chronic infections.…”
Section: The Effect Of Obesity On H Pylori Infectionmentioning
confidence: 99%
“…The biological activities of interleukin-6 contribute to the progression of the atheromatous plaque 24 . In the study of Valezi et al 25 , 20 patients with morbid obesity that underwent bariatric surgery were studied regarding inflammatory markers, indicators of oxidative stress and antioxidant defense.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%